Post-Stratification and Calibration - A Synthesis - Li-Chun Zhang (Statistics Norway, Research Department, 1998)
The paper offers a synthesis of several widely used estimation methods in survey sampling from a rather personal point of view. The methods which will be discussed include post-stratification estimation, generalized regression estimation and calibration estimation. The presentation puts emphasis on understanding, with as little mathematics as possible. It is hoped that in this way anybody, with however varied background of experience with these methods, may find something useful here. The appendix introduces a program package called CALWGT for calibration, which is available on contacting the author.
Keywords: 330; Post-stratification; generalized regression; calibration.